Hubungan Ekspektasi dengan Kepuasan Mahasiswa pada Pelaksanaan Program Merdeka Belajar Kampus Merdeka di Perguruan Tinggi - Vika Ardianti; Sultoni Sultoni; Nurul Ulfatin (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: The objectives of this study are 1) to describe the level of student expectations of the implementation of the MBKM Program in Higher Education, 2) to describe the level of student satisfaction with the implementation of the MBKM Program in Higher Education, 3) to describe the relationship between expectations and the level of student satisfaction with the implementation of the MBKM Program in Higher Education, and 4) to describe the difference between expectations and the level of student satisfaction with the implementation of the MBKM Program in Higher Education. This research is oriented towards quantitative methods. Active students of the State University of Malang and the National Institute of Technology Malang who have participated in the MBKM program with a total of 2665 people are the population in this research. The sampling technique used the Solvin formula with a sample size of 424 respondents. Data collection was done by questionnaire technique. For data collection, the technique used is product moment correlation person. The results of this study indicate that the level of student expectations of the MBKM program at the State University of Malang and the National Institute of Technology Malang is in the medium category with a percentage value of 65.3% and 72.2%. The level of student satisfaction with the MBKM program at the State University of Malang and the National Institute of Technology Malang is in the moderate category with a percentage value of 65.1% and 70.8%. While testing the research hypothesis, namely the relationship between expectations and student satisfaction with the MBKM program at the State University of Malang, getting a calculated r value of 0.996 greater than 0.104, it can be decided that H0 in the study is rejected and Ha in the study is accepted in other words that there is a relationship between expectations and student satisfaction with the MBKM program at the State University of Malang. Testing the research hypothesis on the relationship between expectations and student satisfaction with the MBKM program at the National Institute of Technology Malang got an r count of 0.742 greater than 0.192 so that it can be decided that H0 in the study is rejected and Ha in the study is accepted in other words that there is a relationship between expectations and student satisfaction with the MBKM program at the National Institute of Technology Malang. Keywords: student expectations, student satisfaction, MBKM program Abstrak: Tujuan dari penelitian ini ialah 1) untuk mendeskripsikan tingkat ekspektasi mahasiswa terhadap pelaksanaan Program MBKM di Perguruan Tinggi, 2) mendeskripsikan tingkat kepuasan mahasiswa terhadap pelaksanaan Program MBKM di Perguruan Tinggi, 3) untuk mendeskripsikan hubungan ekspektasi dengan tingkat kepuasan mahasiswa terhadap pelaksanaan Program MBKM di Perguruan Tinggi, dan 4) untuk mendeskripsikan perbedaan ekspektasi dengan tingkat kepuasan mahasiswa terhadap pelaksanaan Program MBKM di Perguruan Tinggi. Riset ini berorientasi terhadap metode kuantitatif. Mahasiswa aktif Universitas Negeri Malang dan Institut Teknologi Nasional Malang yang telah mengikuti program MBKM dengan jumlah 2665 orang ialah populasi dalam riset ini. Teknik pengambilan sampel menggunakan rumus solvin dengan jumlah sampel sebanyak 424 responden. Pengumpulan data dilakukan dengan teknik kuesioner. Guna pengumpulan data, teknik yang digunakan ialah product moment correlation person. Hasil daripada penelitian ini menunjukkan bahwa tingkat ekspektasi mahasiswa terhadap program MBKM di Universitas Negeri Malang dan Institut Teknologi Nasional Malang berada pada kategori sedang dengan nilai presentase sebesar 65,3% dan 72,2%. Tingkat kepuasan mahasiswa terhadap program MBKM di Universitas Negeri Malang dan Institut Teknologi Nasional Malang berada pada kategori sedang dengan nilai presentase sebesar 65,1% dan 70,8%. Sedangkan pengujian hipotesis penelitian yakni hubungan ekspektasi dengan kepuasan mahasiswa terhadap program MBKM di Universitas Negeri Malang mendapatkan nilai r hitung sebesar 0.996 lebih besar daripada 0.104 dapat diputuskan bahwa H0 pada penelitian ditolak dan Ha pada penelitian diterima dengan artian lain bahwa terdapat hubungan antara ekspektasi dengan kepuasan mahasiswa terhadap program MBKM di Universitas Negeri Malang. Pengujian hipotesis penelitian pada hubungan ekspektasi dengan kepuasan mahasiswa terhadap program MBKM di Institut Teknologi Nasional Malang mendapatkan r hitung sebesar 0.742 lebih besar daripada 0.192 sehingga dapat diputuskan bahwa H0 pada penelitian ditolak dan Ha pada penelitian diterima dengan artian lain bahwa terdapat hubungan antara ekspektasi dengan kepuasan mahasiswa terhadap program MBKM di Institut Teknologi Nasional Malang. Kata kunci: ekspektasi mahasiswa, kepuasan mahasiswa, program MBKM